Renovation and monumentality in social housing: The emblematic case of the Lyon urban area in France - Mongeard, Laëtitia. Autor; Veschambr, Vincent. Autor (IGiPZ PAN, 2019)
Large buildings (towers, large slabs, etc.) dating from 1965 to 1974 are one of the five main targets of the Agence Nationale de la Rénovation Urbaine (French National Agency for Urban Renewal), which has used demolition as a privileged tool of intervention in large social housing complexes (grands ensembles) and degraded condominiums since the early 2000s. Using a corpus of grands ensembles in the urban area of Lyon of interest to the national programme of urban renewal, we sought to verify the intentions displayed at the national level; this urban area has indeed been at the forefront of concerns regarding ’city policy’ since the early 1980s and can be considered emblematic of national policies in this area. We simultaneously examined the methods used to demolish these towers and bars, from explosive demolition to mechanical means. Given their monumentality, these buildings are most restrictive at the technical level, and the means by which the demolition occurs are viewed with the greatest attention, as decision-makers are most vigilant regarding their effects on the inhabitants and on public opinion. The demolition of these high-rise buildings can be analysed in light of technical and normative evolutions (security, recycling) as well as their political and ideological meanings.
24 cm
Keywords: urban renewal; social housing; Lyon (France); monumentality; demolition; towers and slabs